Evaluasi Penerapan Program MBKM Terhadap Kompetensi Mahasiswa Program Studi Akuntansi Dan Administrasi Bisnis Di Politeknik Negeri Manado - Siahaan, Belthasar Trito; Ginting, Wenny Anggeresia; Pangemanan, Shane Anneke (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to evaluate the implementation of the MBKM program in the Manado State Polytechnic environment based on student perceptions or responses. This study describes in detail the implementation of the MBKM program that has been implemented by the Manado State Polytechnic. This study is a quantitative study with a survey design. The results of the study are that there are still many students majoring in accounting and business administration who still do not understand what MBKM is, policies on MBKM and what MBKM programs are. From the MBKM program that has been implemented in the accounting and business administration departments, the activities that are most in demand by students in the accounting department are internships and certified independent studies (MSIB). While in the business administration department, the activity that is most in demand by students is Independent Entrepreneurship (WMK). This is possible because this activity provides the most learning experiences that are correlated with the field of study. In terms of MBKM implementation indicators, the MBKM activities carried out are in accordance with the needs of graduates in the future. This means that the implementation of MBKM activities at the Manado State Polytechnic is currently quite good.